Analysis of differences in eating alone attitude of Koreans by dietary habits and age. (1st September 2020) - Lee, Eun Jung; Lee, Kyung-Ran; Kim, Ju-Yeon
Abstract: This study compares differences in eating alone attitude according to dietary habits and age in Seoul and Gyeonggi-do region in South Korea. Out of total 411 participants, 207(50.4%) were males and 204(49.6%) were females. 30 types of eating alone attitude were identified to perform a factor analysis; further these 30 types of attitudes were categorized into 8 factors termed as: 'enjoyable eating alone', 'eating alone as a daily routine', 'healthy eating alone', 'self-conscious eating alone', 'choose what I want', 'efficient eating alone', 'lonely eating alone', and 'solo dining'. Our investigation on the link between dietary habits and eating alone attitude revealed significant differences in 3 factors out of those 8 factors: healthy eating alone, solo dining, eating alone as a daily routine. The high healthy meal group was found to have less frequency of eating alone. Among people in their 20s and 30s, the low healthy meal group had more population than the high healthy meal group. There was a tendency that the population of the high healthy meal group increases as age rises. Our data indicated that the younger generation eats alone more frequently as a daily routine (p < 0.01), feels freer when eating alone, eats out alone more frequently (p < 0.01). People in their 20s were found to be more positive on eating alone and tended to be willing solo diners. The high healthy meal group did eat alone in a healthy way whereas the low healthy meal group had a negative view on eating alone. Our study aims at providing a good starting point to develop programs for healthy eating alone by finding gaps between healthy and unhealthy eating alone.